Factors influencing variation in investigations after a negative CT brain scan in suspected subarachnoid haemorrhage: a qualitative study. Issue 2 (20th December 2018) - Chu, Kevin; Windsor, Carol; Fox, Jennifer; Howell, Tegwen; Keijzers, Gerben; Eley, Robert; Kinnear, Frances; Furyk, Jeremy; Thom, Ogilvie; Brown, Nathan J; Brown, Anthony F T
Abstract : Introduction: Variation in the approach to the patient with a possible subarachnoid haemorrhage (SAH) has been previously documented. The purpose of this study was to identify factors that influence emergency physicians' decisions about diagnostic testing after a normal CT brain scan for ED patients with a headache suspicious of a SAH. Methods: We conducted an interview-based qualitative study informed by social constructionist theory. Fifteen emergency physicians from six EDs across Queensland, Australia, underwent individual face-to-face or telephone interviews. Content analysis was performed whereby transcripts were examined and coded independently by two co-investigators, who then jointly agreed on the influencing factors. Results: Six categories of influencing factors were identified. Patient interaction was at the forefront of the identified factors. This shared decision-making process incorporated 'what the patient wants' but may be biased by how the clinician communicates the benefits and harms of the diagnostic options to the patient. Patient risk profile, practice evidence and guidelines were also important. Other influencing factors included experiential factors of the clinician, consultation with colleagues and external influences where practice location and work processes impose constraints on test ordering external to the preferences of the clinician or patient. The six categories were organised within a conceptual framework comprising four components: the context, the evidence, the experience and the decision. Conclusions: When clinicians are faced with a diagnostic challenge, such as the workup of a patient with suspected SAH, there are a number of influencing factors that can result in a variation in approach. These need to be considered in approaches to improve the appropriateness and consistency of medical care.